Transformational leadership of physical education instructors and university students' satisfaction with online classes - Cruz, Angelita Bautista; Kim, Hyun-Duck (Frontiers in Psychology, 2023)
This study examined the relationship between the transformational leadership of PE instructors and students' satisfaction in an online PE class. In particular, it aimed to investigate whether the PE instructors' transformational leadership behaviors could predict students' satisfaction toward the class, their PE teacher, and their health and fitness. Furthermore, this study explored these relationships in male and female students. A total of 448 university students (male = 228; female = 220) between the ages of 18 and 22 participated in the study. The results revealed a positive relationship between the transformational leadership behaviors of PE instructors and students' satisfaction with online PE classes. Moreover, male and female students' satisfaction with the teaching of their PE instructor, feelings of fun and enjoyment, and perception of improved health and fitness in their online PE classes varied greatly as they perceived specific behaviors of transformational leadership from their PE instructors. These findings demonstrate that PE instructors play an important role as (online) classroom leaders in enhancing students' satisfaction with online learning. Therefore, PE instructors should be mindful to demonstrate transformational leadership to improve their effectiveness when conducting online classes.